Environmental effects of ozone depletion and its interactions with climate change: Progress report, 2011 - Andrady, A. L. (2012)
The parties to the Montreal Protocol are informed by three panels of experts. One of these is the Environmental Effects Assessment Panel (EEAP), which deals with two focal issues. The first focus is the effects of increased UV radiation on human health, animals, plants, biogeochemistry, air quality, and materials. The second focus is on interactions between UV radiation and global climate change and how these may affect humans and the environment. When considering the effects of climate change, it has become clear that processes resulting in changes in stratospheric ozone are more complex than believed previously. As a result of this, human health and environmental problems will be longer-lasting and more regionally variable. Like the other panels, the EEAP produces a detailed report every four years; the most recent was published in 2010 (Photochem. Photobiol. Sci., 2011, 10, 173-300). In the years in between, the EEAP produces less detailed and shorter progress reports, which highlight and assess the significance of developments in key areas of importance to the parties. The next full quadrennial report will be published in 2014-2015.